2020
DOI: 10.1038/s41467-020-20137-9
|View full text |Cite|
|
Sign up to set email alerts
|

Direct energy transfer from photosystem II to photosystem I confers winter sustainability in Scots Pine

Abstract: Evergreen conifers in boreal forests can survive extremely cold (freezing) temperatures during long dark winter and fully recover during summer. A phenomenon called “sustained quenching” putatively provides photoprotection and enables their survival, but its precise molecular and physiological mechanisms are not understood. To unveil them, here we have analyzed seasonal adjustment of the photosynthetic machinery of Scots pine (Pinus sylvestris) trees by monitoring multi-year changes in weather, chlorophyll flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 66 publications
5
65
0
Order By: Relevance
“…This might reflect that water supply as opposed to temperature a key factor affecting the physiological activity of moss species [40]. These three species had high Stern-Volmer type NPQ except in October, reaching a stationary phase with a statistically smaller and overall slower amplitude of the fast component, and instead, the quantum yield of those non-regulated were high, which strongly suggested the fraction of absorbed light energy neither drove photochemistry (Y(II)) nor thermally dissipated by rapid regulated Stern-Volmer type NPQ processes [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might reflect that water supply as opposed to temperature a key factor affecting the physiological activity of moss species [40]. These three species had high Stern-Volmer type NPQ except in October, reaching a stationary phase with a statistically smaller and overall slower amplitude of the fast component, and instead, the quantum yield of those non-regulated were high, which strongly suggested the fraction of absorbed light energy neither drove photochemistry (Y(II)) nor thermally dissipated by rapid regulated Stern-Volmer type NPQ processes [35].…”
Section: Discussionmentioning
confidence: 99%
“…They gained the best photochemical quantum yield in the months of most rainfall or relative humidity and reached more than 75%, even 90% for H. plumaeforme and P. inflexum of the maximal photosynthesis rate even under the driest and lowest rainfall of October, despite a lower photosynthetic efficiency. The results of Y(NO) showed the reversed responses, having the non-regulated heat dissipation lowest and highest in the wet and dry months, respectively, and NPQ always had high and fast components of non-photochemical quenching values to dissipate the excess energy to protect the photosynthesis apparatus [20,21,34,35]. H. plumaeforme from 900 m showed high Stern-Volmer NPQ, which indicated the sufficient capacity of photoprotective reaction [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Chlamydomonas, PsbS was first found under UV light stress [100] and to date it is known to regulate qE together with LhcSR3 in high light conditions [138,139]. Moreover, in conifers, the phosphorylated isoform of the PsbS homologue has been reported to facilitate sustained winter quenching [26] together with direct energy transfer [27]. It has also been demonstrated that the overexpression of PsbS in tobacco increases wateruse efficiency due to a reduced stomatal opening in response to light, resulting in promoted growth in field conditions [140] (Figure 3).…”
Section: Photosystem II Subunit S (Psbs)mentioning
confidence: 99%
“…Over the following ten years, several reviews have compiled evidence of the roles of different Lhc proteins [22][23][24]. In the last decade, several Lhc proteins have been identified and their possible roles have also been elucidated in several additional species [6,[25][26][27]. In this review, an updated comprehensive summary of the evolution, structural and functional properties of light-harvesting antenna proteins are discussed in the context of their possible roles in plant acclimation and adaptation to fluctuating environmental conditions and how the diversity in light-harvesting antennae is linked to the evolution of photosynthetic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…A decay associated spectra analysis was unsuccessful, because we could not simultaneously fit both wild type and soq1 roqh1 properly (depending on which time component we constrain, it was either too long for soq1 roqh1 or too short for wild type). A model including τavg and spectral information could be created (see for a recent example (Bag et al, 2020)) to test whether quenching of PSII is due to energy transfer at PSI (through charge separation from P700 or thermal dissipation by P700 + ), a process referred to as spillover, or quenching at both PSII and PSI is due to thermal dissipation at LHCII. Although we cannot investigate the fluorescence decays as early as ~5 ps due to the longer (30-40 ps) instrument response function (IRF), we observed that the normalized fluorescence decays of wild type and soq1 roqh1 at 710 nm are almost the same before 100 ps (Fig.…”
Section: Possible Additional Energy Dissipation Routes For Qhmentioning
confidence: 99%